Tantangan Mahasiswa Muslim dalam Menjaga Konsistensi Ibadah di Lingkungan Kampus - Ilham Bissalam; Aisyah Inaya Putri; Syadhita Queena Christya; Tyara Safitri; Abdul Fadhil (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
This article examines the challenges faced by Muslim students in maintaining the consistency of their worship in a dynamic campus environment. These challenges arise from the density of academic schedules, difficulties in performing routine worship, and suboptimal time management. To identify the components that influence the consistency of worship, this research utilizes a qualitative method, where data is collected through literature study and observation. The findings indicate that Muslim students need to develop themselves and devise effective strategies to worship amidst campus busyness. By understanding these challenges, it is hoped that Muslim students can better maintain the quality of their worship and enhance their awareness of the importance of spirituality in daily life.